Estrogenic and Progestational Activity of Roots of Rubia cordifolia - PARIAL, S.D.; SHARMA, D.K.; MISTRY, SUNIL; MIDDHA, ANIL; AGARWAL, KAPIL (Asian Journal of Chemistry, 2010)
The estrogenic and progestational activity of the fractionated precipitate of root of Rubia cordifolia were studied on estrous cycle and implantation in old female albino rats. It enhances heat phase in the estrous cycle and exhibited estrogenic and progestational activity without exhibiting any toxic manifestation.